FORMATION OF PERFORMANCE SKILLS IN THE CLASSROOM MAIN INSTRUMENT (PIANO) - Chebotarenko, O.V. (Pedagogy of Higher and Secondary Education, 2006)
In clause conditions of development of pianistic performing skills of the future teachers of music are considered. The typology of performing skills and ways of their formation is offered.